Aspherical‐Atom Modeling of Coordination Compounds by Single‐Crystal X‐ray Diffraction Allows the Correct Metal Atom To Be Identified. Issue 2 (13th November 2014) - Dittrich, Birger; Wandtke, Claudia M.; Meents, Alke; Pröpper, Kevin; Mondal, Kartik Chandra; Samuel, Prinson P.; Amin SK, Nurul; Singh, Amit Pratap; Roesky, Herbert W.; Sidhu, Navdeep
Abstract Single‐crystal X‐ray diffraction (XRD) is often considered the gold standard in analytical chemistry, as it allows element identification as well as determination of atom connectivity and the solid‐state structure of completely unknown samples. Element assignment is based on the number of electrons of an atom, so that a distinction of neighboring heavier elements in the periodic table by XRD is often difficult. A computationally efficient procedure for aspherical‐atom least‐squares refinement of conventional diffraction data of organometallic compounds is proposed. The iterative procedure is conceptually similar to Hirshfeld‐atom refinement (Acta Crystallogr. Sect. A 2008, 64, 383–393; IUCrJ. 2014, 1, 61–79), but it relies on tabulated invariom scattering factors (Acta Crystallogr. Sect. B 2013, 69, 91–104) and the Hansen/Coppens multipole model; disordered structures can be handled as well. Five linear‐coordinate 3d metal complexes, for which the wrong element is found if standard independent‐atom model scattering factors are relied upon, are studied, and it is shown that only aspherical‐atom scattering factors allow a reliable assignment. The influence of anomalous dispersion in identifying the correct element is investigated and discussed.